Synthesis of [18F]FAZA Using Nosyl and Iodo Precursors for Nucleophilic Radiofluorination - Sun, William; Falzon, Cheryl; Naimi, Ebrahim; Akbari, Ali; Wiebe, Leonard I.; Tandon, Manju; Kumar, Piyush (Current Radiopharmaceuticals, 2019)
Background: 1-α-D-(5-Deoxy-5-[18F]fluoroarabinofuranosyl)-2-nitroimidazole ([18F]FAZA) is manufactured by nucleophilic radiofluorination of 1-α-D-(2’,3’-di-O-acetyl-5’-O-toluenesulfonylarabinofuranosyl)- 2-nitroimidazole (DiAcTosAZA) and alkaline deprotection to afford [18F]FAZA. High yields (>60%) under optimized conditions frequently revert to low yields (<20%) in large scale, automated syntheses. Competing side reactions and concomitant complex reaction mixtures contribute to substantial loss of product during HPLC clean-up. Objective: To develop alternative precursors for facile routine clinical manufacture of [18F]FAZA that are compatible with current equipment and automated procedures. Methods: Two new precursors, 1-α-D-(2’,3’-di-O-acetyl-5’-O-(4-nitrobenzene)sulfonyl-arabinofuranosyl)-2- nitroimidazole (DiAcNosAZA) and 1-α-D-(2’,3’-di-O-acetyl-5’-iodo-arabinofuranosyl)-2-nitroimidazole (DiAcIAZA), were synthesized from commercially-available 1-α-D-arabinofuranosyl-2-nitroimidazole (AZA). A commercial automated synthesis unit (ASU) was used to condition F-18 for anhydrous radiofluorination, and to radiofluorinate DiAcNosAZA and DiAcIAZA using the local standardized protocol to manufacture [18F]FAZA from AcTosAZA. Results: DiAcNosAZA was synthesized via two pathways, in recovered yields of 29% and 40%, respectively. The nosylation of 1-α-D-(2’,3’-di-O-acetyl-arabinofuranosyl)-2-nitroimidazole (DiAcAZA) featured a strong competing reaction that afforded 1-α-D-(2’,3’-di-O-acetyl-5’-chloro-arabinofuranosyl)-2- nitroimidazole (DiAcClAZA) in 55% yield. Radiofluorination yields were better from DiAcNosAZA and DiAcIAZA than from DiAcTosAZA, and the presence of fewer side products afforded higher purity [18F]FAZA preparations. Several radioactive and non-radioactive by products of radiofluorination were assigned tentative chemical structures based on co-chromatography with authentic reference compounds. Conclusion: DiAcClAZA, a major side-product in the preparation of DiAcNosAZA, and its deprotected analogue (ClAZA), are unproven hypoxic tissue radiosensitizers. DiAcNosAZA and DiAcIAZA provided good radiofluorination yields in comparison to AcTosAZA and could become preferred [18F]FAZA precursors if the cleaner reactions can be exploited to bypass HPLC purification.
Keywords: nucleophilic substitution